2023
DOI: 10.1021/acs.inorgchem.3c02682
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Bismuth–Antimony–Europium Cluster-Imbedded Polyoxotungstate and Its Bidirectional Luminescence Detection

Sen Yang,
Tiantian Gong,
Yongchao Dai
et al.

Abstract: 124H 2 O (1) was prepared. The polyoxoanion skeleton of 1 contains a Krebstype polyoxotungstate [W 4 O 10 ][B-β-BiW 9 O 33 ] 2 } 14− ({Bi 2 W 22 }) (1a) as a linker that offers six active coordinate O atoms (two μ 3 -O and four μ 2 -O atoms) to grasp two Bi−Sb−Eu cluster-imbedded tungsten-oxo clusters {[Bi 5.35 Sb 0.65 Eu 3 O 9 (H 2 O) 9 ][B-α-SbW 9 O 33 ] 3 } 18− (1b) through Bi−O−W and Sb−O−W bonds. 1b comprises an unprecedented nonanuclearity Bi−Sb−Eu [Bi 5.35 Sb 0.65 Eu 3 O 9 (H 2 O) 9 ] 9+ cluster encircl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…62 Recently, they prepared an unprecedented Eu-POM aggregate as a bidirectional detection probe to continuously recognize both Mn 2+ (on–off) and CO 3 2− (off–on), succinctly summarized as an “on–off–on” mode. 98…”
Section: Photoluminescent Applicationsmentioning
confidence: 99%
“…62 Recently, they prepared an unprecedented Eu-POM aggregate as a bidirectional detection probe to continuously recognize both Mn 2+ (on–off) and CO 3 2− (off–on), succinctly summarized as an “on–off–on” mode. 98…”
Section: Photoluminescent Applicationsmentioning
confidence: 99%
“…Each trimeric subunit is established by 1 SbW 9 O 33 ({SbW 9 }), 1 SeW 9 O 33 ({SeW 9 }), and 1 Se 1/2 Sb 1/2 W 9 O 33 ({Se 1/2 Sb 1/2 W 9 }) fragments encapsulating a hexanuclear Ln-W-oxo cluster Ln 2 W 4 O 9 (H 2 O) 4 ({Ln 2 W 4 }). In contrast to the widely reported POMs constructed by a single species of lacunary fragment, the aggregates containing the lacunary POMs with different heteroatoms are exceedingly rare. , To the best of our knowledge, 1 – 4 are the first POM clusters that contain different types of trivacant Keggin fragments ({SbW 9 }, {SeW 9 }, and {Se 1/2 Sb 1/2 W 9 }) and simultaneously exist μ 2 -{SeO 2 (OH)} as bridging groups to achieve the integration of the whole molecular structure. In addition, studies on the catalytic properties indicated that compound 3 , as a heterogeneous catalyst, is capable of the selective catalytic oxidation of various sulfides and sulfur mustard simulant 2-chloroethyl ethyl sulfide (CEES) in the presence of the environmentally friendly oxidant H 2 O 2 .…”
Section: Introductionmentioning
confidence: 96%
“…14,15 Among them, the luminescent MOFs can be used to detect different types of analytes because of the highly effective and contactless luminescent tests. 7,16,17 MOFs surpass other common chemosensor materials because of their highly flexible architectures and fascinating chemical properties. 18 However, the works on the detection of THF are less reported.…”
Section: Introductionmentioning
confidence: 99%